The influence of vulture restaurants on breeding success and nestling body condition of Gyps vulture populations across southern Africa - Zimunya, Tapiwa (Department of Biological Sciences, 2019)
Vulture populations in many parts of the world continue to decline owing to numerous threats, such as lack of adequate food sources, poisoning and collisions with power-lines. Worldwide, supplementary feeding sites (hereafter, vulture restaurants) have been used as a conservation tool aimed at supporting vulture populations. However, in many parts of the world there is little scientific evidence about their effectiveness in aiding vulture populations. Here, I assessed the relationship between chick condition (African White-backed Vultures) and breeding success (Cape Vultures/African White-backed Vultures) in relation to a variety of variables which described levels of access to vulture restaurants. My data suggest the potential of vulture restaurants to increase breeding success in vulture populations. Breeding success generally increased for nests closer to vulture restaurants. There was a significant positive correlation between African White-backed Vulture breeding success and proximity to vulture restaurants (p< 0.05), but little evidence to support such a relationship for Cape Vultures (p> 0.05). Nestling body condition of African White-backed Vultures was also not influenced by proximity to vulture restaurants (p> 0.05). Findings of this study provide motivation on the use of vulture restaurants as a conservation strategy across southern Africa. The current study informs future conservation efforts on the use of vulture restaurants across the region, particularly in countries where a network of vulture restaurants is still being established.